2011
DOI: 10.4000/ejrieps.4580
|View full text |Cite
|
Sign up to set email alerts
|

Analyser l’activité décisionnelle de joueurs de football en situation d’entraînement pour développer un modèle de joueur virtuel

Abstract: Cette activité décisionnelle a été appréhendée à l'aide du cadre théorique de la NDM en situation aménagée à des fins d'étude. Des données comportementales ont été enregistrées auprès de douze joueurs de football, puis complétées par des données verbales recueillies lors d'un entretien d'autoconfrontation. Les données ont été analysées en 6 étapes : (a) la retranscription des données, (b) la sélection et l'identification des unités significatives, (c) le découpage du déroulement de l'activité en situations véc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Within the broader sports domain, the RPD model has been applied to provide insight into the decision making of players in soccer (Bossard, Kermarrec, De Keukelaere, Pasco, & Tisseau, 2011; Kermarrec & Bossard, 2014), ice hockey (Bossard, De Keukelaere, Cormier, Pasco, & Kermarrec, 2010; Mulligan, McCracken, & Hodges, 2012), and volleyball (Macquet, 2009). Results have identified that players across different sports exhibit a similar breakdown in the strategies used to make a decision—that is, they use similar V1/V2/V3 ratios; for instance, participants have been found to exhibit V1 (simple match) strategies between 80% and 85% of the time (for a summary, see Kermarrec & Bossard, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the broader sports domain, the RPD model has been applied to provide insight into the decision making of players in soccer (Bossard, Kermarrec, De Keukelaere, Pasco, & Tisseau, 2011; Kermarrec & Bossard, 2014), ice hockey (Bossard, De Keukelaere, Cormier, Pasco, & Kermarrec, 2010; Mulligan, McCracken, & Hodges, 2012), and volleyball (Macquet, 2009). Results have identified that players across different sports exhibit a similar breakdown in the strategies used to make a decision—that is, they use similar V1/V2/V3 ratios; for instance, participants have been found to exhibit V1 (simple match) strategies between 80% and 85% of the time (for a summary, see Kermarrec & Bossard, 2014).…”
mentioning
confidence: 99%
“…Despite this growing body of research in sport, it is unknown whether OiS follow similar decision-making strategies to athletes in general (i.e., Bossard et al, 2011; Macquet, 2009; Mulligan, McCracket, & Hodges, 2012) or perhaps use more considered and evaluative strategies, similar to defensive soccer players (Kermarrec & Bossard, 2014). When investigating OiS performance, naturalistic research has examined factors influencing decision making, albeit without reference to the RPD model.…”
mentioning
confidence: 99%
“…Those situations would led the users to make decisions and to coordinate their decisions to be more efficient. For example, the CoPeFoot simulator is a soccer simulator, in which the design model of virtual agents is the result of an analytical work on the activities of real football players during a practice (Bossard et al, 2011). A VR system, such as the CopeFoot, can be helpful in order to facilitate shared understanding.…”
Section: Simulation and Context Sharingmentioning
confidence: 99%
“…Considering the interest of VR simulation for coordination training, the CoPeFoot simulator was extended to ExpeCoPeFoot, designed in order to display the information the users take in account when interacting with the environment (Bossard et al, 2011). The first stage consisted in playing a game.…”
Section: Sharing Context and Displaying Team Members' Focusmentioning
confidence: 99%
See 1 more Smart Citation